What does a mouse tell us about neuregulin 1—cannabis interactions? - Karl, Tim; Arnold, Jonathon C. (Frontiers in Cellular Neuroscience, 2013)
The link between cannabis and psychosis has been debated although there is substantial epidemiological evidence showing that cannabis increases the risk of psychosis. It has been hypothesized that schizophrenia patients carrying particular risk genes might be more sensitive to the psychosis-inducing effects of cannabis than other patients and healthy test subjects. Here we review the effects of cannabinoids on a mutant mouse model for the schizophrenia candidate gene neuregulin 1 (Nrg1). The studies suggest a complex interaction between cannabis and Nrg1: the neuro-behavioural effects of cannabinoids were different in Nrg1 mutant and control mice and depended on exposure time, sex and age of test animals. This research provides the first evidence of complex cannabis-Nrg1 interactions suggesting Nrg1 as a prime target for future clinical investigations. Furthermore, it highlights that animal model research can broaden our understanding of the complex multi-factorial aetiology of schizophrenia. Finally, the findings are important to preventive psychiatry: if the genes that confer genetic vulnerability to cannabis-induced psychosis were identified patients at-high risk could be forewarned of the potential dangers of cannabis abuse.